Preparation and Bioevaluation of a Novel 99mTc-Labeled Glucose Derivative Containing Cyclohexane as a Promising Tumor Imaging Agent - Junhong Feng; Xuran Zhang; Yuhao Jiang; Qing Ruan; Qianna Wang; Junbo Zhang (MDPI AG, 2023)
To develop novel tumor imaging agents with high tumor uptake and excellent tumor/non-target ratios, a glucose derivative containing cyclohexane (CNMCHDG) was synthesized and labeled with Tc-99m. [99mTc]Tc-CNMCHDG was prepared by a kit formulation that was straightforward to operate and fast. Without purification, [99mTc]Tc-CNMCHDG had a high radiochemical purity of over 95% and great in vitro stability and hydrophilicity (log P = −3.65 ± 0.10). In vitro cellular uptake studies showed that the uptake of [99mTc]Tc-CNMCHDG was significantly inhibited by pre-treatment with D-glucose and increased by pre-treatment with insulin. Preliminary cellular studies have demonstrated that the mechanism by which the complex enters into cells may be related to GLUTs. The results of biodistribution and SPECT imaging studies displayed high tumor uptake and good retention of [99mTc]Tc-CNMCHDG in A549 tumor-bearing mice (4.42 ± 0.36%ID/g at 120 min post-injection). Moreover, [99mTc]Tc-CNMCHDG exhibited excellent tumor-to-non-target ratios and a clean imaging background and is a potential candidate for clinical transformation.